Development of polymeric nanocomposite hydrogel using poly (vinyl alcohol) reinforced with organically modified layered double hydroxides for drug delivery systems - Mohd Sebri, Nor jannah (2022)
A new advanced polymeric material with a potential for drug delivery systems was developed using the versatile poly (vinyl alcohol), PVA, enhanced with layered double hydroxides (LDH) organically modified with sodium dodecyl sulfate (SDS) and sodium isethionate (Ise) via co-precipitation method.